Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

sin theta + sin phi = a cos theta + cos phi = b theta- phi = alpha eliminate theta and phi

sin theta  + sin phi = a
cos theta + cos phi = b
theta- phi = alpha
eliminate theta and phi

Grade:11

1 Answers

mohan
33 Points
3 years ago
sin(theta) +sin(phi)=a implies 2sin((theta +phi)/2)cos((theta-phi)/2)=a “equation1” similarly 2cos((theta+phi)/2)cos((theta-phi)/2)=b “equation 2” on dividing both equations we have tan((theta+phi)/2)=a/b implies sin((theta+phi)/2)=a/(a2+b2)1/2 substituting in equation  one we have cos(alpha/2)=(a2+b2)1/2/2

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free